POTENCY OF ANTICANCER COMPOUNDS FROM THE InaCC LIPI COLLECTION Actinomycetes WERE ANALYZED USING antiSMASH - Annisa Khumaira; Tsania Taskia Nabila (BIOEDUKASI, 2021)
Every year cancer cases have always increased. According to WHO data, in 2020, there were 19.2 million cases of cancer. Cancer treatment is still developing by exploring medicinal compounds that have a minimal risk to healthy cells but can still kill cancer cells. Secondary metabolites from the phylum Actinomycetes are often explored to determine their usefulness, one of which is an anticancer compound. The InaCC project from LIPI has several collections of Actinomycetes that have never been explored, mainly novel species obtained in the 2011-2016 timeframe. The purpose of this study was to analyze the genomic sequences of the InaCC Actinomycetes collection using antiSMASH to determine the potential of the compounds for anticancer. First, the genome sequence data search was carried out through the NCBI gene bank, then analyzed the sequences using antiSMASH 5.0, after searching for the compounds' potential through publication search using the ChEMBL Database and Google Scholar. In the NCBI database, all bacterial phylum Actinomycetes InaCC 2011-2016 have not found any genomic sequence data to use bacteria with the closest relationship for antiSMASH analysis. The closest relatives' analysis results showed that BGC compounds that can have anticancer properties in the bacterial collection of the phylum Actinomycetes InaCC 2011-2016 include terpenes butyrolactol, furans, alkyresorcinol, desferroxamine, and siderophore. These results indicate that the phylum Actinomycetes bacteria could have BGC anticancer compounds and could be developed to treat cancer. The analysis of this research needs to be confirmed again if each bacterium's genomic sequence is complete.